IMPLEMENTASI OLAHRAGA TRADISIONAL SEBAGAI MEDIA PEMBELAJARAN BERBASIS BUDAYA LOKAL PADA PEMBELAJARAN PJOK DI SEKOLAH DASAR - La Robi; Muh. Mawardi; Budiman; Irfandi Idris; La Ode Muhammad Rino Zulkahar (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Physical Education, Sports, and Health (PJOK) learning in elementary schools is still predominantly oriented toward modern sports, resulting in the underutilization of traditional sports as a local culture-based learning medium. In fact, traditional sports have considerable potential to develop fundamental movement skills, foster character development, and preserve local cultural heritage. This study aimed to describe the implementation of traditional sports as a local culture-based learning medium in Physical Education, Sports, and Health (PJOK) learning at the elementary school level. The study employed a qualitative approach using a library research method. Data were collected from scientific journal articles, books, and relevant policy documents indexed in Scopus, Web of Science, ERIC, Google Scholar, Crossref, and Garuda databases. Data were gathered through document analysis and analyzed using thematic analysis. The findings indicate that traditional sports, such as gobak sodor, engklek, bentengan, egrang, bakiak, and tug of war, effectively support the achievement of fundamental movement competencies, enhance physical literacy, improve learning motivation and active participation, and promote character values such as cooperation, sportsmanship, discipline, responsibility, and mutual cooperation. Furthermore, the implementation of traditional sports contributes to the preservation of local culture through contextual and meaningful learning experiences. However, its implementation continues to face challenges, including limited teacher competence, a lack of local culture-based instructional materials, and inadequate facilities and infrastructure. Therefore, strengthening teachers' competencies, developing instructional modules, and providing institutional policy support are essential to ensure the sustainable implementation of traditional sports in elementary school Physical Education, Sports, and Health (PJOK) learning.